Synthesis of O-Hydroxypropyl-N-Alkylated Chitosans and Characterization of Their Surface Features - Lin, Qiang; Wang, Xuying; Dong, Ankang; Cui, Yumei; Huo, Qing (Asian Journal of Chemistry, 2012)
A class of novel amphiphilic chitosan derivates, the polymeric surfactant O-hydroxypropyl-N-alkyl chitosans (Cn-HPCS), was synthesized by first modifying chitosan into the more hydrophilic O-hydroxypropyl chitosan and then alkylating the amino groups with different long carbon chains. The structures were characterized using 1H NMR and FT-IR and several surface activity parameters, including surface tension, critical micelle concentration (CMC), hydrophile-lipophile balance (HLB), foam characteristics and emulsibility, were measured. The critical micelle concentration values ranged from 0.016 g/L to 0.05 g/L and the hydrophile-lipophile balance values were between 5.33 and 13.89. The structures displayed good foam characteristics and the emulsibility was better than that of Tween 60. Because of these good surface activity properties, the Cn-HPCS have many potential surfactant applications.